AB0334 COST-EFECTIVENESS OF JAK INHIBITORS IN RHEUMATOID ARTHRITIS IN THE REAL WORL PRACTICE. (2nd June 2020) - Calvo Garcia, A.; García Castañeda, N.; Valero, C.; Llorente, I.; Varas, B.; García-Vadillo, A.; González-Álvaro, I.; Morell, A.; Ramirez, E.; Garcia de Vicuna, R.
Abstract : Background: The Janus Kinase (JAK) inhibitors Baricitinib (BAR) and Tofacitinib (TOF), both in monotherapy or in combination with methotrexate, are indicated for moderate to severe active rheumatoid arthritis (RA) with inadequate response to conventional synthetic disease modifying anti-rheumatic drugs (csDMARD). Data about cost-effectiveness in a real-world setting are still scarce. Objectives: To assess the cost-effectiveness (C-E) of BAR and TOF in patients with RA in usual clinical practice. Methods: Retrospective observational study of adult RA patients who started BAR and TOF between September 2017 and December 2019, in a university hospital. Data were collected from the electronic medical records and the Dominion® External Patient Dispensing program. Demographic, clinical and laboratory parameters [erytrocyte sedimentation rate (ESR), C reactive protein (CRP), Rheumatoid factor (RF), anti-citrullinated peptide antibodies (ACPA)], concomitant csDMARD, previous biological (b) DMARD, DAS28-ESR activity score items, and treatment duration were registered. DAS28-ESR remission or low disease activity (LDA) were used as the effectiveness measure to estimate C-E. The official Spanish prices were considered to calculate the costs of the treatments. Statistical analysis was performed with SPSS v.15 program. Descriptive statistics are shown in proportions, medians and interquartile ranges (IQR). The Wilcoxon signed ranges test was applied for the changes from baseline of DAS28-ESR and CRP. Results: 39 patients were included, 87.2% women, median age 62.9 (49.9-74.4) years. 9/39 patients (23.1%) were naive to bDMARD, 6 (15.4%) had received 1, 18 (46.1%) 2, and 6 (15.4 %) ≥3 previous bDMARD. Demographic, clinical and effectiveness characteristics are shown by drug in the Table: Regarding BAR, 17 patients (56.6%) continue on treatment and 3 (10%) changed to TOF. The change in DAS28VSG was statistically significant (p = 0.000), as well as difference in CRP (p = 0.008). The total cost per analysed period was € 357, 806.40, with 18/30 patients (60%) achieving remission or LDA. The C-E was € 19, 878.13. As for TOF, 6 patients (66.6%) remain on drug, with no switch to BAR. Neither the difference from baseline in DAS28VSG nor the CRP changes reached statistical significance (p = 0.08 and p = 0.735, respectively). The total cost per analysed period was € 90, 201.72, with 4/9 patients (44.4%) achieving remission or LDA. The C-E was € 22, 573.0 Conclusion: In our daily practice, JAK inhibitors are mainly used in combination with csDMARD and commonly after failure to ≥ 1 bDMARD. In this real setting, BAR proves to be cost-effective, while TOF renders less effectiveness. However, results should be addressed with caution because of the smaller sample size of TOF population. Additional studies with greater follow-up and sample size are needed to confirm these findings. Disclosure of Interests: Alberto Calvo Garcia: None declared, Noelia García Castañeda: None declared, Cristina Valero: None declared, Irene Llorente Speakers bureau: Lilly, Janssen, Novartis, Sanofi, Gebro, Blanca Varas: None declared, Alberto García-Vadillo: None declared, Isidoro González-Álvaro Grant/research support from: Roche Laboratories, Consultant of: Lilly, Sanofi, Paid instructor for: Lilly, Speakers bureau: Abbvie, MSD, Roche, Lilly, Alberto Morell: None declared, Esther Ramirez: None declared, Rosario Garcia de Vicuna Grant/research support from: BMS, Lilly, MSD, Novartis, Roche, Consultant of: Abbvie, Biogen, BMS, Celltrion, Gebro, Lilly, Mylan, Pfizer, Sandoz, Sanofi, Paid instructor for: Lilly, Speakers bureau: BMS, Lilly, Pfizer, Sandoz, Sanofi